The texts and versions of the book of Ben Sira: transmission and interpretation ; [the symposium took place in Metz on October 15 - 17, 2009] - Rey, Jean-Sébastien (Journal for the study of Judaism / Supplements, 2011)
An alternative Hebrew form of Ben Sira : the anthological manuscript C / Jeremy Corley -- Reconstructions and retroversions : chances and challenges to the Hebrew Ben Sira text / P.C. Beentjes -- Wordplay in the Hebrew to Ben Sira / E.D. Reymond -- Animal imagery in the Hebrew text of Ben Sirach / N. Calduch-Benages -- Translation Greek in Sirach in light of grandson's proplogue / Benjamin G. Wright III -- The literary attainment of the translator of Greek Sirach / J.K. Aitken -- Le métier de scribe, un métier différent / Franc̜oise Vinel -- Archaic elements in the Syriac version of Ben Sira / Jan Joosten -- Christian features in the Peshitta of Ben Sira : the question of dependency on the Syriac New Testament / Robert J. Owens -- The Old Latin version of Sirach ; editio critica and textual problems / Anthony J. Forte -- La version latine de Ben Sira / Thierry Legrand -- The additions to Ben Sira and the book's multiform textual witness / Jason Gile -- L'espérance post-mortem dans les différentes versions du Siracide / Jean-Sébastien Rey -- La prière de Ben Sira dans les manuscrits hébreux et dans les versions anciennes / Maria Carmela Palmisano -- La sagesse dans les béatitudes de Ben Sira : étude dutexte de Si 51,13-30 et de 14,20-15,10 / Émile Puech